Critical thinking as a necessity for social science students capacity development: How it can be strengthened through project based learning at university - Witarsa,; Muhammad, Syahril (Frontiers in Education, 2023)
Critical thinking is a necessity to students, because it empowers them in solving problems, especially during learning and also in the real-life situation within society. Based on this, the present research proposes a citizenship project model which aims to improve Elementary School Teacher Education Study Program by emphasizing critical thinking among students during the teaching of Civic Education at universities in Indonesia. The research is experimental quasi-research which comprised of two classes, that is the experimental class and control class. The two classes were conducted with the purpose to compare the effectiveness of the proposed citizenship project learning model. The data analysis techniques used was a Statistical Program for Social Science. To attain the required results in regard to the implementation of the citizenship project learning model, there were several stages, including: problem identification, problem formulation, information gathering, documenting the process, showcasing of the results and reflective analysis of the model implementation process. The final results revealed a significant improvement in critical thinking abilities of the students in experimental class compared to the control class category. Thus, it is concluded that the adoption of a citizenship project learning model is appropriate for critical thinking skills improvement of the students taking citizenship education study program at university.